Efectos socio-jurídicos e impacto ambiental derivado de la falta de control a la fumigaciones aéreas en el Banano, el cantón El Guabo periodo 2012-2013. - Pauta Pacheco, Lilia Pamela (2013)
One concern is the degradation of the ecosystem and diversity, which then can no longer be recovered such natural resources of the area that for years have suffered the consequences of environmental impact, which helps the career development of the area and will serve for future generations.